2006
DOI: 10.1515/jpem.2006.19.5.713
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Cardiomyopathy in Children and Adolescents with Type 1 Diabetes Mellitus: Association of Echocardiography Indicators with Duration of Diabetes Mellitus and Metabolic Parameters

Abstract: This study was designed to determine the relationship of dimensions, wall thickness and function of the left ventricle with diabetes duration, fasting blood glucose, lipid profile, beta-OH-butyrate, free fatty acids (FFA) and carnitine levels in children and adolescents with type 1 diabetes mellitus (DM1) who had no cardiovascular complications. Thirty-five patients with DM1 (18 F/17 M, mean age: 12.0 years) and age matched control children (n = 24) were enrolled in the study. Patients with DM1 were subdivided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
5
14
0
Order By: Relevance
“…The present results are in agreement with data reported by some other authors 13,14,17 and point to the presence of early, still asymptomatic signs of impaired cardiac muscle relaxation and compliance in diabetic patients, the consequence of which might be found in cardiac muscle functional and morphological abnormalities observed in adult patients with type 1 diabetes. This is the more likely in that these patients demonstrate signs of cardiac muscle dysfunction without the presence of any additional, traditional risk factors, such as hypertension, disturbances of lipid metabolism or coronary atheromatosis 18 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present results are in agreement with data reported by some other authors 13,14,17 and point to the presence of early, still asymptomatic signs of impaired cardiac muscle relaxation and compliance in diabetic patients, the consequence of which might be found in cardiac muscle functional and morphological abnormalities observed in adult patients with type 1 diabetes. This is the more likely in that these patients demonstrate signs of cardiac muscle dysfunction without the presence of any additional, traditional risk factors, such as hypertension, disturbances of lipid metabolism or coronary atheromatosis 18 .…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study seem to confirm this thesis, while they indicate a significant effect of prolonged hyperglycemia defined by the mean HbA1c values calculated for the entire treatment duration and for the two years prior to the study on development of negative changes in the cardiac diastolic function. While analyzing echocardiographic parameters, we have not demonstrated their dependence on the degree of metabolic control in the last three months prior to the study, which was in agreement with observations reported by other authors 2,13,14 . On the other hand, the analysis of the association between cardiac morphology and function and long-and medium term metabolic control showed a significant effect of unsatisfactory metabolic control in both these periods on the increase of IRT and dimension of the posterior LV wall during the systole in the girls, as well as the A wave value in both genders.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Though our patients with longer disease duration had poorer glycemic control and higher serum cholesterol, they did not manifest any significant changes in the carotid artery parameters, similar to data reported by Gunczler et al [28]. Conversely few other authors have identified early cardiac changes in the presence of longer diabetes duration [29, 30]. …”
Section: Discussionsupporting
confidence: 89%
“…In the present study, though there was a trend for patients with LVH to have the level of HbAlc to be higher (9.5±0.8%) than those without LVH (8.5±1.5%), but this trend was not significant statistically. Other authors also reported that there is no correlation between HbA1c and the development of cardiovascular changes in children and adolescents with type I DM, which is similar to results of the current study (21,26). In the same previous study, Giunti et al (21), reported that left ventricular systolic function was comparable in both diabetics and controls which was the same result obtained in our study.…”
Section: Discussionsupporting
confidence: 92%